# How to find the Laplace transform of the following function: f(t)=te^t F(s)=int_0^(oo)(te^t e^(-st))dt What method do I use to find the integral?

How to find the Laplace transform of the following function:
$f\left(t\right)=t{e}^{t}$
$F\left(s\right)={\int }_{0}^{\mathrm{\infty }}\left(t{e}^{t}{e}^{-st}\right)dt$
What method do I use to find the integral?
You can still ask an expert for help

## Want to know more about Laplace transform?

• Questions are typically answered in as fast as 30 minutes

Solve your problem for the price of one coffee

• Math expert for every subject
• Pay only if we can solve it

Kamden Simmons
We have:
$f\left(t\right)=t{e}^{t}$
So the Laplace transform of this function is:
$\begin{array}{rl}F\left(s\right)& =\mathcal{L}\left\{f\left(t\right)\right\}\\ & ={\int }_{0}^{\mathrm{\infty }}f\left(t\right){e}^{-st}\phantom{\rule{thinmathspace}{0ex}}dt\\ & ={\int }_{0}^{\mathrm{\infty }}t{e}^{t}{e}^{-st}\phantom{\rule{thinmathspace}{0ex}}dt\\ & ={\int }_{0}^{\mathrm{\infty }}t{e}^{\left(1-s\right)t}\phantom{\rule{thinmathspace}{0ex}}dt\\ & =\underset{b\to \mathrm{\infty }}{lim}\left[{\int }_{0}^{b}t{e}^{\left(1-s\right)t}\phantom{\rule{thinmathspace}{0ex}}dt\right]\\ & =\underset{b\to \mathrm{\infty }}{lim}\left({\left[t\cdot \frac{1}{1-s}{e}^{\left(1-s\right)t}\right]}_{t=0}^{b}-{\int }_{0}^{b}\frac{1}{1-s}{e}^{\left(1-s\right)t}\phantom{\rule{thinmathspace}{0ex}}dt\right)\\ & =\frac{1}{1-s}\underset{b\to \mathrm{\infty }}{lim}\left(b{e}^{\left(1-s\right)b}-{\int }_{0}^{b}{e}^{\left(1-s\right)t}\phantom{\rule{thinmathspace}{0ex}}dt\right)\\ & =\frac{1}{s-1}\underset{b\to \mathrm{\infty }}{lim}{\int }_{0}^{b}{e}^{\left(1-s\right)t}\phantom{\rule{thinmathspace}{0ex}}dt& \left(s>1\right)\\ & =\frac{1}{s-1}\underset{b\to \mathrm{\infty }}{lim}{\left[\frac{1}{1-s}{e}^{\left(1-s\right)t}\right]}_{0}^{b}& \left(s>1\right)\\ & =\frac{1}{\left(s-1{\right)}^{2}}\underset{b\to \mathrm{\infty }}{lim}\left[1-{e}^{\left(1-s\right)b}\right]& \left(s>1\right)\\ & =\frac{1}{\left(s-1{\right)}^{2}}& \left(s>1\right)\end{array}$